Automatic derivation of kinematic equations for robotic manipulators on the bases of formalized description of their kinematic chains; The 9th International Forum on Strategic Techology (IFOST-2014), September 21-23, 2014, Cox's Bazar, Bangladesh - Yakovlev A. S. (Publication Only Papers, 2014)
Title screen